Analisis Yuridis Pengisian Jabatan Wakil Kepala Daerah Dalam Penyelenggaraan Pemerintahan Daerah - Tri Suhendra Arbani (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2017)
This research, which has a title " juridical analysis of fulfillment of the absenceof deputy chief of major’s position the implementation of local government” has purposeto analyze mechanism the fulfillment of the absence of deputy chief of major’sposition the implementation of local government, as well as the implications of emptinessof the absence of deputy chief of major’s position the implementation of local government.This research is normative juridical research. Data collection in this research usecollaborative methods between literature research to collect secondary data in law and tocollect supporting data for literature research. Data was analyzed by qualitativedescriptive analysis. Based on analysis in this research, shows that: First, TheMechanism of Filling the Deputy Head of Region is done in the perspective ofGovernment Regulation Number 49 of 2008 regarding the third amendment toGovernment Regulation Number 6 Year 2005 regarding the Election, Approval,Appointment and Dismissal of Regional Head and Deputy Head of Region, Second,The direct impact to the community due to the absence of a deputy head of the region canbe seen from the heavy workload of regional heads in managing local governments thathave many problems where it can not be resolved without the help of a representative, sothat many services and development will be disrupted.